Financial Frictions: Micro versus Macro Volatility - Faccini, Renato; Lee, Seungcheol; Luetticke, Ralph; Ravn, Morten O.; Renkin, Tobias (American Economic Review, 2026)
We argue that consumer credit spreads matter for household choices and that time-varying spreads have important distributional consequences. Studying Danish household data, we show that consumer credit spreads have heterogeneous impact on asset dynamics and consumption choices across the wealth distribution and that time-varying spreads induce a countercyclical marginal propensity to consume. We study a HANK model where banks provide consumer credit and corporate loans. Through countercyclical credit spreads, frictional finance amplifies aggregate shocks and induces consumption inequality. Economies with less leveraged banks experience reduced aggregate volatility but may face higher volatility and lower welfare at the household level. (JEL D12, D31, E12, E21, E32, E52, G51)